2018
DOI: 10.1111/risa.13190
|View full text |Cite
|
Sign up to set email alerts
|

sCARy! Risk Perceptions in Autonomous Driving: The Influence of Experience on Perceived Benefits and Barriers

Abstract: The increasing development of autonomous vehicles (AVs) influences the future of transportation. Beyond the potential benefits in terms of safety, efficiency, and comfort, also potential risks of novel driving technologies need to be addressed. In this article, we explore risk perceptions toward connected and autonomous driving in comparison to conventional driving. In order to gain a deeper understanding of individual risk perceptions, we adopted a two‐step empirical procedure. First, focus groups (N=17) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 55 publications
4
47
0
Order By: Relevance
“…In addition, risk assessments in autonomous driving technology were found to be influenced by the prior experience with technology in general and the experience with driver assistance systems 1 (Brell et al 2019d;2019c).…”
Section: Technology Acceptance and Innovation Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, risk assessments in autonomous driving technology were found to be influenced by the prior experience with technology in general and the experience with driver assistance systems 1 (Brell et al 2019d;2019c).…”
Section: Technology Acceptance and Innovation Managementmentioning
confidence: 99%
“…With increasing knowledge of and experience with automated driving systems, risk perceptions towards autonomous driving decreased and acceptance of the technology increased (Brell et al 2019d;2019c;Ward et al 2017). Apparently, the familiarity with the handling of advanced speed regulation systems increased the trust perceptions in the reliability and safety of the system, and the discomfort towards the autonomous (uncontrollable) nature of the system decreased.…”
Section: Technology Acceptance and Innovation Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomous vehicles (AVs), also known as ‘robotic’, ‘driverless’ or ‘self-driving’ vehicles, evolved from the preceding advanced driving assistant system and had improved target distinguishing arithmetic, route planning and active control. It is anticipated that AVs will be a revolutionary technological innovation with the potential to lower the permit threshold of driving, reduce travel costs, mitigate environmental pollution and improve road safety 6–8. A survey showed that the public were likely to be receptive to AVs when provided with information relating to public health benefits 9.…”
Section: Introductionmentioning
confidence: 99%
“…Risk and benefit perceptions were also key variables in Brell, Philipsen, and Ziefle's () contribution. Using a two‐step empirical approach of focus groups and a survey, they explored risk perceptions of connected and autonomous vehicles in comparison to conventional driving and found that autonomous driving was perceived as riskier than conventional driving.…”
mentioning
confidence: 99%